2004
DOI: 10.1037/0893-3200.18.3.545
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Shared Environment in Infant-Father Attachment: A Behavioral Genetic Study of the Attachment Q-Sort.

Abstract: In this first behavior genetic study on infant-father attachment, we estimated genetic and environmental influences on infant-father attachment behaviors and on temperamental dependency, both assessed with the Attachment Q-Sort (AQS; B. E.Vaughn & E. Waters, 1990;E. Waters, 1995). Mothers of mono-and dizygotic twins (N ϭ 56 pairs) sorted the AQS with a focus on the infant's behaviors in the presence of the father. Genetic modeling showed that attachment was largely explained by shared environmental (59%) and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 37 publications
5
38
0
5
Order By: Relevance
“…In contrast with adult studies, twin studies in infants and preschoolers found modest (O'Connor & Croft, 2001) or negligible (Bakermans-Kranenburg, van Ijzendoorn, Bokhorst, & Schuengel, 2004;Bokhorst et al, 2003;Roisman & Fraley, 2008) genetic influence on attachment. A similar conclusion was reached by Ricciuti (1992), who combined the samples of some small pioneer studies of 12-to 22-month-old twins assessed with the SS and did not find evidence of genetic influence.…”
Section: Discussionmentioning
confidence: 78%
“…In contrast with adult studies, twin studies in infants and preschoolers found modest (O'Connor & Croft, 2001) or negligible (Bakermans-Kranenburg, van Ijzendoorn, Bokhorst, & Schuengel, 2004;Bokhorst et al, 2003;Roisman & Fraley, 2008) genetic influence on attachment. A similar conclusion was reached by Ricciuti (1992), who combined the samples of some small pioneer studies of 12-to 22-month-old twins assessed with the SS and did not find evidence of genetic influence.…”
Section: Discussionmentioning
confidence: 78%
“…This small sample technique provides depth rather than generalizability and is particularly appropriate for sensitive topic research. 35,[39][40][41][42] Qmethodology has been extensively used in qualitative psychological research to understand human behavior, 39,[43][44][45][46] workplace behaviors, 41,47 among others. Therefore, in a relatively unexplored area like PWU, this technique can provide insights into the underlying dynamics of perceptions of the actors.…”
Section: Methodsmentioning
confidence: 99%
“…The other available twin studies of attachment have all tested for heritable effects in children (Bakermans-Kranenburg, van IJzendoorn, Schuengel, & Bokhorst, 2004;Bokhorst et al, 2003;O'Connor & Croft, 2001). These studies used different assessment methods that include the Strange Situation (Ainsworth et al, 1978), the Attachment Q-Sort (Vaughn & Waters, 1990;Waters, 1995) and Cassidy and Marvin's (1992) preschool coding manual for behaviour in the Strange Situation.…”
Section: Attachment and Personality Disordermentioning
confidence: 99%